2017
DOI: 10.22159/ijpps.2017v9i7.14189
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on Prescribing Trends and Adverse Drug Reactions in Stroke Patients

Abstract: Objective: To evaluate medication use pattern and adverse drug reactions (ADRs) among stroke patients admitted in Neurology department of a multi-speciality hospital.Methods: A prospective observational study was carried out for a period of 6 mo, in a 750 bedded multi-speciality hospital in Bangalore. The clinical pharmacist analysed the medication use pattern and occurrence of ADRs in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…According to the World Health Organization, "stroke is a clinical syndrome characterized by rapidly developing clinical symptoms and/ or signs of focal, and at times global (applied to patients in deep coma and those with SAH), loss of cerebral function, with symptoms lasting more than 24 hrs or leading to death, with no apparent cause other than that of vascular origin [4]. Spontaneous ICH is one of the diseases when intracranial blood vessels ruptured, and the neurologic deficits will appear due to the neuron cells dead [5].…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, "stroke is a clinical syndrome characterized by rapidly developing clinical symptoms and/ or signs of focal, and at times global (applied to patients in deep coma and those with SAH), loss of cerebral function, with symptoms lasting more than 24 hrs or leading to death, with no apparent cause other than that of vascular origin [4]. Spontaneous ICH is one of the diseases when intracranial blood vessels ruptured, and the neurologic deficits will appear due to the neuron cells dead [5].…”
Section: Discussionmentioning
confidence: 99%
“…Increased stroke patient is one interesting topic that draws the attention of researchers [1]. One type of stroke commonly found is intracerebral hemorrhage (ICH).…”
Section: Research Articlementioning
confidence: 99%
“…Another study on 60 stroke patients revealed about 7.01% patients were given citicoline [10]. Previous studies on citicoline examined its effectiveness on many conditions i.e.…”
Section: Introductionmentioning
confidence: 99%